Pengendalian Hama Kutu Daun Coklat pada Tanaman Cabe mengggunakan Pestisida Organik Ekstrak Serai Wangi - Fahruddin Arfianto (​Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2016)
Cultivation of chili is a farming activity promising an interesting profits and the market demand for the chili is high. Many chili farmers in controlling pests use chemical pesticides because it is considered more efficient and fast, actually the chemical pesticides do not kill insects’ pests, but it creates a new form of defense for insects’ pests. In another effort to find alternative pesticides are expected to be more lenient, then developing the manufacture of pesticides made from natural materials exist around the neighborhood, known by name